Effects of respiratory muscle training on respiratory function, exercise capacity, and quality of life in chronic stroke patients: a systematic review and meta-analysis - Huang, Lang; Zhang, Jia-Mei; Bi, Zi-Ting; Xiao, Jing-Hua; Wei, Jing-Xue; Huang, Jian; Luo, Chao-Song; Li, Ying-Dong; Zhang, Yue-Mi; Zhang, Yun-Shan (Frontiers in Physiology, 2025)
BackgroundRespiratory muscle training is a structured intervention targeting the respiratory muscles, yet its effect on chronic stroke patients remains unclear. The study evaluated the influence of this training on respiratory function, exercise capacity and quality of life among individuals who experienced chronic strokes.MethodsThis study adhered to the PRISMA statement guidelines. A comprehensive search of databases including PubMed, Embase, AMED, CINAHL, Cochrane Library, and Web of Science was conducted without date limitations, extending until 8 March 2025. The search targeted randomised controlled trials that involved: 1) chronic stroke patients (≥18 years, diagnosed for >3 months), 2) respiratory muscle training encompasses both inspiratory and expiratory muscle training, and 3) outcomes measuring the strength and endurance of respiratory muscle, pulmonary function testing, exercise capacity, and quality of life. Two separate reviewers conducted the screening for eligibility, gathered data, and evaluated both the methodological quality and potential risk of bias. Meta-analyses utilized RevMan version 5.4 (Cochrane Collaboration, United Kingdom), applying random-effects models to calculate mean difference (MD), standardized mean difference (SMD), and corresponding 95% confidence intervals (95% CI).ResultsNine studies were included, comprising 288 participants (143 males and 145 females) with a mean age of 58.5 years. For primary outcomes, respiratory muscle training significantly enhanced maximal inspiratory pressure (MD = 17.71 cmH2O, 95% CI: 10.19–25.23) and respiratory muscle endurance (MD = 20.58 cmH2O, 95% CI: 12.25–28.92) among chronic stroke patients, but no significant effects were observed for maximal expiratory pressure (MD = 11.37 cmH2O, 95% CI: −0.78–25.23). The subgroup analysis revealed that the combination of inspiratory muscle training and expiratory muscle training enhanced maximal inspiratory pressure (MD = 23.47 cmH2O, 95% CI: 3.65–43.30) and respiratory muscle endurance (MD = 34.00 cmH2O, 95% CI: 21.21–46.79), while inspiratory muscle training improved maximal inspiratory pressure (MD = 14.09 cmH2O, 95% CI: 7.57–20.62), maximal expiratory pressure (MD = 8.69 cmH2O, 95% CI: 0.63–16.75), and respiratory muscle endurance (MD = 16.69 cmH2O, 95% CI: 10.27–23.11). For secondary outcomes, significant improvements occurred in forced expiratory volume in 1s (MD = 0.25 L, 95% CI: 0.06–0.44) and peak expiratory flow (MD = 0.84 L/s, 95% CI: 0.31–1.37), but not in forced vital capacity (MD = 0.16 L, 95% CI: −0.08–0.41), exercise capacity (SMD = 0.29, 95% CI: −0.03–0.61), and quality of life.ConclusionRespiratory muscle training effectively enhances primary outcomes, including maximal inspiratory pressure and respiratory muscle endurance, as well as secondary outcomes such as forced expiratory volume in 1s and peak expiratory flow in chronic stroke patients, but does not improve maximal expiratory pressure, forced vital capacity, exercise capacity, and quality of life. The combination of inspiratory muscle training with expiratory muscle training, as well as inspiratory muscle training alone, can enhance maximal inspiratory pressure and the endurance of respiratory muscles. Furthermore, inspiratory muscle training alone can improve maximal expiratory pressure.Systematic Review Registrationidentifier, CRD42024517859.